MENINGKATKAN KETERAMPILAN MENULIS TEKS PERSUASI MENGGUNAKAN MEDIA GAMBAR - Monalisa, Mega; Priyadi, Antonius Totok; Abdussamad, Abdussamad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research was motivated by researcher"™s findings that students"™ skill of SMP Negeri 12 Ketungau Tengah in writing persuasive text was low. It was evidenced when the researcher did the pre-research. She found that the score obtained by only three students who achieved score more than or equal to 75 which is Minimum Completeness Criteria set by the school. In addition, the cause of these problems that students were never introduced to any learning media. The method used in this research was descriptive with qualitative and quantitative research. The object of this research was 18 students of grade VII of SMPN 12 Ketungau Tengah. The data in this research was in the form of a description of planning, implementation, and student test result sheets about the skills of writing persuasive texts using pictures media. Data collection techniques used in this study was direct observation and test. The results showed that there was an improvement from first cycle to second cycle. In pre-action stage, it found that students"™ mean score was only 1.188,89 or 66.05. Afterwards, the researcher applied pictures as a learning media and found that the students"™ mean score in first cycle was 1.297,13 or 72.06, it increased to 1.459,83 or 81.17 in the second cycle. This proves that pictures can improve students"™ learning outcomes in writing persuasive texts. In conclusion, based on the result of this research, it indicates that students need teacher"™s creativity and motivation in teaching and learning process